An abdominal wound dehiscence of emergency explorative laparotomy and their management at tertiary care centre: an observational study - Modi, Jenish; Patel, Yash; Trivedi, Mitesh; Bochiya, Girish (International Surgery Journal, 2023)
Background: Wound dehiscence is a very troublesome sequel of impaired wound healing. Despite of medical advances frequency of wound dehiscence in emergency laparotomy remains high due to multiple factors together predisposes. Better understanding of common mechanisms and highly contributing factors will help to keep high risk patients under strict surveillance to reduce the incidence of wound dehiscence. Methods: The observational study was carried out in 167 patients of above 14 years age at the department of General surgery, SMIMER hospital, Surat between November 2018 to October 2020 Result: 22.15% patients developed wound dehiscence, mean age in dehiscence group was 39.27±9.65 years. Abdominal pain was found in all the patients 100% followed by vomiting 28.74% and fever 13.17%. However, Fever (2.37±1.95 days vs 1.55±1.78 days) and Abdominal distention (1.05±1.06 days vs 0.47±0.87) have statistical significance between Wound Dehiscence and No Wound Dehiscence regarding chief complaints. As a treatment of wound dehiscence, 2 (5.40%) had Re-exploration and 6 (16.21%) had Re-exploration and Tension Suturing in complete wound dehiscence patient group and 29 (78.39%) had Secondary suturing found in partial wound dehiscence. 5.40% of mortality found in Wound Dehiscence group. Conclusions: Significant risk factors for abdominal wound dehiscence identified in this study are presenting complains like fever and abdominal distension, pre-operative hypoalbuminemia, pre-operative anemia, leucocytosis, renal dysfunction, intra-abdominal sepsis. Use of subcutaneous negative tube is protective for the condition. Hollow viscus perforation patients showed higher vulnerability for wound dehiscence.